Zhongguo jin dai si xiang jia wen ku - Yun, Daiying; Liu, Hui (Zhongguo ren min da xue chu ban she, 2014)
Summary in vernacular field only
"Yun Daiying nian pu jian bian"--Pages 537-556
Keywords: Youth / China / Conduct of life; Communism / China; Communism; Youth / Conduct of life; Jugend; Kommunismus; China